Pengaruh Metode Islah Mubasyir terhadap Kedisiplinan Santri Pondok Pesantren Al-Basyariyah Kabupaten Bandung - Akhmad Rizkon (Program Pascasarjana Universitas Ibrahimy, 2019)
Islah mubasyir is a method of punishment carried out by Pondok Pesantren Al-Basyariyah (Al-Basyariyah Islamic Boarding School) in Bandung Regency. It has applied since the beginning of the establishment of this Islamic boarding school. It was addressed to offender students and the punishment was given directly. It was applied to minimize students’ delinquency in Pondok Pesantren Al-Basyariyah, so the students have awareness in discipline. This method aims to improve students’ awareness of discipline in all matters. The application of islah mubasyir also includesthe influence, inhibiting and supporting factors. The purpose of this study was to obtain the information regarding the application, the influence, inhibiting and supporting factors of islah mubasyir at Pondok Pesantren Al-Basyariyah in Bandung Regency.